Dynamic analysis of Iran's oil and gas exports and sales revenue in the time horizon of 2050 - Paria Samadi Parviznejad; Ali Mohaghar (تصمیم گیری و تحقیق در عملیات)
Purpose: The main purpose of this paper is a dynamic analysis of oil and gas exports and sales income in 2050. A dynamic system is needed to forecast the export and sales of oil in the future, which requires considering the cause-and-effect relationships between the variables affecting the main research problem.Methodology: This paper is applied in terms of purpose, which uses dynamic system modeling to create the model.Findings: Two positive causal loops of oil and gas sales growth and oil and gas field capacity utilization growth, and three negative causal loops of capacity limitations in oil and gas fields, limitations in oil and gas field capacity utilization, and the third was created with the limitation of access to oil resources. Also, three optimistic, moderate, and pessimistic scenarios were simulated in the dynamic system model. In the first scenario, the simulation was performed based on the changes in the oil price parameter in the future. In this scenario, oil and gas exports grew by 38%. In the second scenario, the income from exports showed an eight-fold growth optimistically. Finally, in the pessimistic scenario, the graphs showed that the values of the state variables remained constant. Finally, the validation was done using the analysis of different scenarios for the dynamic system model.Originality/Value: In this paper, in addition to the dynamic analysis of the factors influencing oil and gas industry variables, the time effects of these changes have also been considered. Previous studies have only used economic development variables to predict the future of the oil and gas industry. In this paper, the values of other variables, such as production capacity, existing reservoirs, and market risk, are considered as the main variables in the dynamic model for scenarios in the time horizon of 2050.